Treating Penile Cancer in the Immunotherapy and Targeted Therapy Era - Gavin Hui; Sanaz N. Ghafouri; John Shen; Sandy Liu; Alexandra Drakaki (Case Reports in Oncological Medicine)
While localized penile cancers are typically treated surgically and metastatic penile cancers benefit from standard chemotherapy, there have been studies on the horizon demonstrating immunotherapy as a novel approach to metastatic penile cancers that have failed standard chemotherapy. We report a case series of two patients who improved on immunotherapy after progressing with standard chemotherapy regimens. The first case describes a 64-year-old male with a penile mass and significant lymphadenopathy who had surgical resection and adjuvant chemotherapy prior to continued disease progression. He was started on anti-EGFR treatment and improved initially, but he eventually had progression of disease. The second case describes a 79-year-old male with a penile mass who was treated with surgical resection and started on adjuvant chemoradiation, but he developed recurrence and nodal involvement. Therefore, second-line therapy of the PD-L1 inhibitor was started in this patient. There were no available clinical trials for penile cancer patients who progressed beyond the standard surgical therapy and chemotherapy.